Optical properties of layers and crystals of spherical particles - A. Modinos; V. Karathanos; N. Stefanou (Applied Surface Science, 1993)
We have developed a formalism which allows one to calculate the transmission, reflection and ansorbance of electromagnetic waves by structures having two-dimensional periodicity parallel to a given surface. The structures considered are single layers or multilayers of non-overlaping spheres, embedded in a host material of different dielectric function. A special case of multilayer is a stack of identical layers whose properties, when the thickness of the slab exceeds a certain limit, are identical with those of the corresponding infinite crystal. We present numerical results for specific examples of single layers and multilayers, and point out some interesting physics which came out of our calculations.